2017
DOI: 10.1007/s00066-017-1139-4
|View full text |Cite
|
Sign up to set email alerts
|

T1–2 glottic cancer treated with radiotherapy and/or surgery

Abstract: Despite a possible selection bias, our series demonstrates improved RFS with RT over surgery in stage I glottic SCC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
25
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 23 publications
(28 citation statements)
references
References 46 publications
1
25
0
Order By: Relevance
“…According to the latest NCCN guidelines, surgery or definitive radiotherapy can be used for curing T1‐2N0M0 LSCC. Several studies have demonstrated improved survival with radiation over surgery . Survival benefit in patients with early‐stage LSCC undergoing surgery has also been reported in a number of other studies .…”
Section: Introductionmentioning
confidence: 74%
See 1 more Smart Citation
“…According to the latest NCCN guidelines, surgery or definitive radiotherapy can be used for curing T1‐2N0M0 LSCC. Several studies have demonstrated improved survival with radiation over surgery . Survival benefit in patients with early‐stage LSCC undergoing surgery has also been reported in a number of other studies .…”
Section: Introductionmentioning
confidence: 74%
“…Briefly, patients with labeled primary sites C32.0-Glottis, C32.1-Supraglottis, C32.2-Subglottis, C32.3-Laryngeal cartilage, C32.8-Overlapping lesion of larynx, or C32.9-Larynx NOS were included. Exclusion criteria were as follows: (1) not SCC; (2) without positive histology confirmation; (3) not the first tumor; (4) not stage I or stage II; (4) chemotherapy received; (5) underwent both radiotherapy and surgery; (6) not beam radiation if radiotherapy administered. Conversion from the old version to the seventh AJCC TNM staging system was performed manually.…”
Section: Data Selectionmentioning
confidence: 99%
“…Today, a vast amount of clinical experience from single‐institution trials as well as prospective clinical trials on primary organ preserving treatment is available . Multimodality organ‐preservation treatment has become the treatment of choice for many tumor entities .…”
Section: Introductionmentioning
confidence: 99%
“…A recent analysis revealed an overall incidence of tracheostomies in patients with advanced laryngeal and hypopharyngeal cancer undergoing chemoradiotherapy (CRT) of 34% . The CRT protocols for laryngeal cancer allow the preservation of the organ with good locoregional disease control . Despite this organ preservation strategy, a high number of patients with head and neck cancer remain dependent on a feeding tube and tracheostomy .…”
Section: Introductionmentioning
confidence: 99%
“…2 The CRT protocols for laryngeal cancer allow the preservation of the organ with good locoregional disease control. 3,4 Despite this organ preservation strategy, a high number of patients with head and neck cancer remain dependent on a feeding tube and tracheostomy. 5 Radiotherapy (RT) causes fibrosis and edema, which may lead to an impaired laryngeal mobility and airway obstruction, requiring a life-saving tracheostomy.…”
Section: Introductionmentioning
confidence: 99%